Longitudinal bidirectional relation between fear of missing out and risky loot box consumption: Evidence for FoMO-Driven loot boxes spiral hypothesis - Andree Hartanto; K.T.A.Sandeeshwara Kasturiratna (Computers in Human Behavior Reports)
Background: The integration of loot boxes has emerged as a significant factor contributing to the increasing revenue in the video gaming industry. However, this integration has also led to widespread engagement in risky loot box consumption. To understand the mechanism that drives and sustains such maladaptive behavior, we propose the FoMO-Driven Loot Boxes Spiral Hypothesis – positing that fear of missing out (FoMO) not only triggers initial engagement in risky loot box consumption but also perpetuates a self-reinforcing cycle, where such engagement intensifies subsequent FoMO, leading to further risky loot box consumption. Method and results: We conducted a 13-week longitudinal study of 252 college students with weekly data collection to examine the bidirectional relation. Using random-intercept cross-lagged panel models, we found significant small-to-moderate cross-lagged effects from FoMO to risky loot box consumption and significant moderate-to-large cross-lagged effects from risky loot box consumption to FoMO. Implications: Our findings support FoMO as an important trigger for initiating risky loot box consumption. Moreover, once players start engaging with risky loot box consumption, they often find themselves trapped in a reinforcing cycle of FoMO and risky loot box consumption. These findings contributes to our understanding of problematic behavior in digital gaming and have implications for the development of targeted interventions and policies aimed at reducing risky loot box consumption.